Purkinje Cell Pathology and Loss in Multiple Sclerosis Cerebellum. (31st December 2014) - Redondo, Juliana; Kemp, Kevin; Hares, Kelly; Rice, Claire; Scolding, Neil; Wilkins, Alastair
Abstract: Cerebellar ataxia commonly occurs in multiple sclerosis, particularly in chronic progressive disease. Previous reports have highlighted both white matter and grey matter pathological changes within the cerebellum; and demyelination and inflammatory cell infiltrates appear commonly. As Purkinje cell axons are the sole output of the cerebellar cortex, understanding pathologic processes within these cells is crucial to develop strategies to prevent their loss and thus reduce ataxia. We studied pathologic changes occurring within Purkinje cells of the cerebellum. Using immunohistochemic techniques, we found changes in neurofilament phosphorylation states within Purkinje cells, including loss of dephosphorylated neurofilament and increased phosphorylated and hyperphosphorylated neurofilament. We also found Purkinje axonal spheroids and Purkinje cell loss, both of which occurred predominantly within areas of leucocortical demyelination within the cerebellar cortex. These changes have important implications for the study of cerebellar involvement in multiple sclerosis and may help design therapies to reduce the burden of ataxia in the condition.